A new chestnut-feeding species of Stomaphis Walker (Hemiptera: Aphididae: Lachninae) from Korea - Lee, Minho; Kanturski, Mariusz; Lee, Seunghwan (Zootaxa, 2022)
A new aphid species, Stomaphis (Stomaphis) blackmani sp. nov., is described on the basis of specimens collected on the chestnut tree, Castanea crenata Siebold & Zucc. (Fagaceae) from Korea. The apterous and alate viviparous female of the new species are described with biometric measurements and illustrations. Being the first report of Stomaphis on chestnut worldwide, a brief note on the biology of the new species, and a key to Stomaphis species in the Korea Peninsula is provided.